Pelatihan Guru dan Orang Tua dalam Menumbuhkan Kebiasaan Digital Sehat serta Pencegahan Kekerasan pada Anak Usia Dini di Desa Cikedokan - Srianita, Yossi; Rahmi, Azi Matur (Universitas Pahlawan Tuanku Tambusai, 2026)
The main focus of early childhood stimulation is direct interaction with parents, real play and exploration of the surrounding environment, but based on initial observations many parents have given gadgets since an early age, and use digital media without parental supervision. The background of this activity is driven by the increasing use of digital devices by early childhood which has the potential to cause negative impacts such as: addiction, exposure to content that is not appropriate for the age and development of children, to the risk of physical and sexual violence in children in the real world and digitally. The implementation method includes: 1) socialization 2) interactive training, 3) mentoring for teachers and parents to develop parenting and learning patterns oriented towards healthy digital literacy and character education. The expected results of community service activities are an increase in participants' knowledge on how to guide children in using technology wisely, instill moral values and build positive communication between home and school.